The Effect Of Sale Proneness On Consumer Response To Quitline-Based Smoking Quit Service Advertisements - Mohammad Sulkifli (Pasundan Social Science Development, 2026)
This study aims to analyze the effect of sales proneness on consumer responses to quitline-based smoking cessation service advertisements. Smoking behavior remains a serious public health problem in Indonesia and globally, so effective communication strategies are needed to encourage behavior change, one of which is through public service advertisements combined with quitline services. This study uses a quantitative approach with a survey method and explanatory research design to test the causal relationship between the sales proneness variable as the independent variable and consumer responses as the dependent variable. Data were collected through a Likert-scale questionnaire from respondents who had been exposed to smoking cessation service advertisements, then analyzed using validity and reliability tests, descriptive analysis, and simple linear regression. The results showed that sales proneness had a positive and significant effect on consumer responses with a significance value of 0.000 < 0.05 and a regression coefficient of 0.65. In addition, the coefficient of determination (R²) value of 0.420 indicates that sales proneness is able to explain 42% of the variation in consumer responses, while the rest is influenced by other factors outside the study. These findings indicate that individuals with a high propensity for persuasive stimuli respond more readily to smoking cessation advertisements, both in terms of attention, attitude, and behavioral intention. Therefore, psychological factors such as sales proneness are crucial in designing more effective and targeted health communication strategies to support smoking reduction efforts in the community.